2003
DOI: 10.1002/tl.108
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Tensions of Problem‐Based Learning: Insights From Research

Abstract: Professors who wish to implement problem‐based learning (PBL) must reconcile numerous tensions regarding its efficacy. The authors address some of these tensions by considering empirical literature about PBL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
57
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 26 publications
1
57
0
Order By: Relevance
“…While Hung et al [21] identified PBL tensions in general, other researchers identified tensions specific to engineering education reform. These include individual versus organization value assigned to teaching [14][27], theory versus practice/application [22], classroom problems (well-structured) versus real-world problems (illstructured) [24], single-disciplinary versus interdisciplinary content [16], problem-solving versus design [24].…”
Section: Tensions That Faculty Encountermentioning
confidence: 98%
See 2 more Smart Citations
“…While Hung et al [21] identified PBL tensions in general, other researchers identified tensions specific to engineering education reform. These include individual versus organization value assigned to teaching [14][27], theory versus practice/application [22], classroom problems (well-structured) versus real-world problems (illstructured) [24], single-disciplinary versus interdisciplinary content [16], problem-solving versus design [24].…”
Section: Tensions That Faculty Encountermentioning
confidence: 98%
“…Hung et al [21] identified and described five tensions of PBL. These include depth versus breadth of curriculum, higher-order thinking versus factual knowledge acquisition, long-term effects versus immediate learning outcomes, student's initial discomfort versus their subsequent positive attitudes, and the traditional role of instructor versus the role of facilitator.…”
Section: Tensions That Faculty Encountermentioning
confidence: 99%
See 1 more Smart Citation
“…Hung, Bailey and Jonassen, (2003) suggest developing group-processing skills is important and Schmidt et al (2007) advise training learners in group collaboration skills before using PBL, so group processes function more effectively and thus reduce cognitive load. The Police PBL facilitators spent considerable time on group processes before and during PBL, encouraging us to reflect on our group interactions to promote effective teamwork and interpersonal communication.…”
Section: Achieving Guidance In a Police Pbl Classroommentioning
confidence: 99%
“…For example, it is important for tutors to encourage problem-solving processes and meta-cognitive thinking (Hung et al, 2003;Loftus & Higgs, 2005). We discussed meta-cognition early in the course and were encouraged to build on this concept through our learning journals.…”
Section: Achieving Guidance In a Police Pbl Classroommentioning
confidence: 99%